The Influence of Teachers' Social Competence on Student Resilience at Santo Fransiscus Xaverius Kema Catholic High School - Jearne Felix Imbang; Ansyela Fransiska Kaunang; Wasia Saleh; Petra Anjelus Rompas (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to determine: (1) the social competence of teachers at Santo Fransiscus Xaverius Kema Catholic High School, (2) the resilience of students at Santo Fransiscus Xaverius Kema Catholic High School, (3) the extent to which teacher social competence influences student resilience at Santo Fransiscus Xaverius Kema Catholic High School. This study used quantitative methods. The sampling technique used was saturated sampling, which consisted of 57 teachers and students. The instrument used was a questionnaire consisting of variable X and variable Y. The collected data were analyzed using descriptive statistical analysis to test hypotheses 1 and 2 and simple linear regression analysis to test hypothesis 3. The results of the study prove that the teacher's social competence coefficient reached 0.90, while the student's resilience coefficient reached 0.83, both of which are in the very good category. Further findings show that there is an influence of teacher social competence on student resilience, with the magnitude of the influence indicated by a correlation coefficient value of 0.075. Based on these results, the author concludes that the influence of teacher social competence on student resilience is in the very low category with a percentage of 7.5%.